French Baroque Opera: A Reader - Sadler, Graham; Wood, Caroline (Aldershot Ashgate, 2000)
From the outset, French opera generated an enormous diversity of literature, familiarity with which enhances our understanding of this unique art form. Yet relatively little of that literature is available in English, despite an upsurge of interest in the Lully-Rameau period. This is a wide-ranging picture of the organization and evolution of French baroque opera, its aims and aspirations, its strengths and weaknesses. Drawing on official documents, theoretical writings, letters, diaries, dictionary entries, contemporary reviews and commentaries, it provides an insight into Lully's once-proud Royal Academy of Music and the colourful characters who surrounded it. The translated passages are set in context, and readers are directed to further scholarly and critical writings in English.
Keywords: Opéra (Paris, France); 17th Century (1601-1700); 18th Century (1701-1800); Opera; France